2004
DOI: 10.1161/01.cir.0000105725.61763.a2
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Experimental Abdominal Aortic Aneurysm in the Rat by Use of Decoy Oligodeoxynucleotides Suppressing Activity of Nuclear Factor κB and ets Transcription Factors

Abstract: Background-Two phenomena, inflammation and matrix degradation, contribute to the progression of abdominal aortic aneurysm (AAA). Importantly, the inflammation is regulated by the transcription factor nuclear factor (NF)-B, whereas the destruction and degradation of elastin fibers by matrix metalloproteinases (MMP) are regulated by ets. Thus, we developed a novel strategy to treat AAA by simultaneous inhibition of both NF-B and ets by using chimeric decoy oligodeoxynucleotides (ODN). Methods and Results-AAA was… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
80
0
1

Year Published

2006
2006
2015
2015

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 97 publications
(86 citation statements)
references
References 40 publications
5
80
0
1
Order By: Relevance
“…46,47 Consistently, we reported previously that ets was induced in experimental AAA, followed by overproduction of MMPs. 19 Interestingly, the present study indicated that high blood pressure significantly upregulated both NFB and ets in a rat AAA model.…”
Section: Shiraya Et Al Hypertension Accelerated Abdominal Aortic Aneumentioning
confidence: 45%
See 2 more Smart Citations
“…46,47 Consistently, we reported previously that ets was induced in experimental AAA, followed by overproduction of MMPs. 19 Interestingly, the present study indicated that high blood pressure significantly upregulated both NFB and ets in a rat AAA model.…”
Section: Shiraya Et Al Hypertension Accelerated Abdominal Aortic Aneumentioning
confidence: 45%
“…To confirm this hypothesis, we used chimeric decoy ODN, because our previous article demonstrated a suppressive effect of decoy ODN on activation of both NFB and ets, 19,23,24 and observed that in vivo transfection of chimeric decoy ODN using a delivery sheet significantly suppressed the upregulation of NFB and ets induced by elastase. 19 First, we used an ex vivo organ culture system of human vascular tissue from aneurysms and examined the effect of chimeric decoy ODN on the expression of MMP-1 and MMP-9, because MMP-1 and MMP-9 are considered to play a pivotal role in the pathogenesis in human AAA. MMP-1, as well as MMP-9, was readily detected in the conditioned medium from the organ culture system.…”
Section: Prevention Of Development Of Aaa By Chimeric Decoy Odn In Hymentioning
confidence: 99%
See 1 more Smart Citation
“…7,26 In addition to the mechanisms above, the functional role of NF-kB that activates MMP-9 expression has been demonstrated in a variety of animal models of abdominal aortic aneurysms. 25,30 A recent paper indicated that activation of NF-kB also appeared at the site of cerebral aneurysm formation. 4 Cerebral aneurysms tend to be formed at the arterial bifurcation by hemodynamic shear stress, and fluid shear stress has been shown to promote the translocation into the nucleus of NF-kB in cultured endothelial cells by activating IkB kinase.…”
Section: Mmpmentioning
confidence: 99%
“…Likewise, studies have demonstrated that AKT2 deficiency 47 and c-Jun N-terminal kinase activation 38 aggregated AAA development, whereas c-Jun is the major target of c-Jun N-terminal kinase pathway. Besides, nuclear factor-κB also has been reported to regulate MMPs and promote the development of experimental AAA 48 via AP-1 activation. p110δ inactivation may mediate these pathways during vascular injury.…”
Section: Discussionmentioning
confidence: 99%